Two New Sulfate-Modified Dibenzopyrones With Anti-foodborne Bacteria Activity From Sponge-Derived Fungus Alternaria sp. SCSIOS02F49 - Chen, Yaping; Liu, Chuanna; Kumaravel, Kaliaperumal; Nan, Lihong; Tian, Yongqi (Frontiers in Microbiology, 2022)
At present, foodborne diseases (FBDs) caused by bacteria are gradually increasing every year, and the development of new antibiotics is an urgent necessity for human beings. To find novel antibacterial compounds, three sponge-derived fungal strains (SCSIOS02F40, F46, and F49) were investigated. As a result, Alternaria sp. SCSIOS02F49 was selected for investigation on its secondary metabolites because its ethyl acetate (EtOAc) extract of potato dextrose broth (PDB) culture showed rich metabolites and strong antibacterial activity. Two new dibenzopyrones with rare sulfate group (1–2), together with 10 known compounds (3–12), were isolated from the Alternaria sp. SCSIOS02F49. Their structures were confirmed by nuclear magnetic resonance (NMR), mass spectrometry (MS) data, and comparison with data from the relevant literature. Almost all compounds showed moderate inhibitory activity against eight foodborne bacteria (FBB) with minimum inhibitory concentration (MIC) values in the range of 15.6–250 μg/ml, and minimum bactericidal concentration (MBC) values in the range of 31.3–250 μg/ml. The antibacterial mechanism of compound 1 was preliminarily investigated using growth curves, scanning electron microscopy (SEM), and flow cytometry (FCM), which revealed that compound 1 altered the external structure of Staphylococcus aureus and caused the rupture or deformation of the cell membranes. This research provides lead compounds for the development of new antibiotics or microbial preservatives.